Isolated plexiform neurofibroma mimicking a vascular lesion - Paola Cecilia Stefano; Sebastian Nicolas Apa; Agustina Maria Lanoël; Josefina Sala María; Sergio Sierre; Adrián Martin Pierini (Sociedade Brasileira de Dermatologia, 2016)
Abstract Plexiform neurofibromas are benign tumors originating from peripheral nerve sheaths, generally associated with Neurofibromatosis Type 1 (NF1). They are diffuse, painful and sometimes locally invasive, generating cosmetic problems. This report discusses an adolescent patient who presented with an isolated, giant plexiform neurofibroma on her leg that was confused with a vascular lesion due to its clinical aspects. Once the diagnosis was confirmed by surgical biopsy, excision of the lesion was performed with improvement of the symptoms.